Fungsi Hukum Dalam Penyelesaian Kasus Bidang Kenotariatan : (Studi Kasus Kode Etik dan Jabatan Notaris) - Aiza, Didha Narin; Nabila, Selma; Ananda, Heppy Trio; Abdullah, Nadhifa; Susmayanti, Riana (Faculty of Law, Universitas Brawijaya, 2024)
In every society, law functions more to ensure security in society and guarantee the achievement of the social structure expected by society. One of them is in the field of notarial science with positive law in the form of laws and implementing regulations. The existence of regulations in Law Number 2 of 2014, Amendment to Law Number 30 of 2004 concerning the Position of Notaries (hereinafter referred to as UUJN) is not necessarily implemented well. There are still many legal problems that occur within and laxities that exist in the regulations for the position of notary, especially in the area of the professional code of ethics. So it is necessary to analyze real cases that have occurred (Das Sein) as well as problems in the regulations (Das Sollen) based on the function of the law itself. So this research produces a theory of the function of law that has an impact on law in the notary field. This research is normative research with a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). From the results and discussion through case studies, the existence of this legal function theory can be used as a reference or benchmark for the implementation of law and legal products related to the notary profession and other public officials who make deeds. As well as meeting or relying on the synergy of the notary itself as a social institution. So that the Notary as a legal implementing factor (person) plays a very important role as a factor in implementing legal functions.